qPCR Analysis Reveals Association of Differential Expression of SRR, NFKB1, and PDE4B Genes With Type 2 Diabetes Mellitus - Raza, Waseem; Guo, Jinlei; Qadir, Muhammad Imran; Bai, Baogang; Muhammad, Syed Aun (Frontiers in Endocrinology, 2022)
Background: Type 2 diabetes mellitus (T2DM) is a heterogeneous, metabolic, and chronic condition affecting vast numbers of the world's population. The related variables and T2DM associations haven't been fully understood due to their diverse nature. However, functional genomics can facilitate understanding of the disease. This information will be useful in drug design, advanced diagnostic, and prognostic markers. Aim: To understand the genetic causes of T2DM, this study was designed to identify the differentially expressed genes (DEG's) of the disease. Methods: We investigated 20 publicly available disease-specific cDNA datasets from Gene Expression Omnibus (GEO) containing several attributes including gene symbols and clone identifiers, GenBank accession numbers, and phenotypic feature coordinates. We analyzed an integrated system-level framework involving gene ontology (GO), protein motifs and co-expression analysis, pathway enrichment, and transcriptional factors to reveal the biological information of genes. A co-expression network was studied to highlight genes that showed a coordinated expression pattern across a group of samples. The differentially expressed genes were validated by qPCR to analyze the expression levels of case and control samples (50 each) using glyceraldehyde 3-phosphate dehydrogenase (GAPDH) as the reference gene. Results: From the list of 50 DEG, we ranked 3 T2DMs-related genes (p-value<0.05) including SRR, NFKB1, and PDE4B. The enriched terms revealed a significant functional role in amino acid metabolism, signal transduction, transmembrane and intracellular transport, and other vital biological functions. DMBX1, TAL1, ZFP161, NFIC (66.7 percent), and NR1H4 (33.3 percent) are transcriptional factors associated with the regulatory mechanism. We found substantial enrichment of insulin signaling and other T2DM-related pathways, including valine, leucine and isoleucine biosynthesis, serine and threonine metabolism; adipocytokine signaling pathway, P13-AKT, and hedgehog signaling pathways. The expression profile of these DEG’s verified by qPCR showed a substantial level of 2-fold change (FC) expression (2-ΔΔCT) in SRR (FC≤0.12), NFKB1 (FC≤1.09), and PDE4B (FC≤0.9) genes compared to controls (FC≥1.6). The downregulated expression of these genes is associated with the pathophysiological development and metabolic disorders. Conclusion: This study would help to modulate the therapeutic strategies for T2DM and could speed up drug discovery outcomes.